Natural Radioprotectors For Oncology: Therapeutic and Diagnostic Prospects - Md Sadikuj Jaman; Md Rokibul Hasan Bhuiyan; Md Maniruzzaman; Mst Tasnova; Sanjida Monira; Md Rakib Rased Rana; Md Nahid Hasan; Dipongkar Ray Sobuj; Tamanna Rashid; Saiful Islam Arif (Journal of Healthcare and Biomedical Science, 2025)
Cancer remains one of the most significant global health challenges, and radiotherapy continues to be one of the most effective treatment options. However, Patients are also exposed to low doses of ionizing radiation during diagnostic procedures such as computed tomography (CT) and magnetic resonance imaging (MRI). These exposures can induce various cellular and molecular defects in the human body. Therefore, there is an urgent need to develop safer and more reliable radioprotective agents to minimize radiation-induced damage. This review was prepared using selected keywords searched across major scientific databases, including Google Scholar, ScienceDirect, PubMed, and Scopus, covering publications from the inception of each database up to October 14, 2025. This review highlights plant-derived radioprotective agents that exhibit antioxidant, anti-inflammatory, immunomodulatory, DNA repair-enhancing, and metal-chelating actions. It outlines the key molecular pathways involved, such as antioxidant defense, DNA repair regulation, and ROS scavenging, and briefly compares natural compounds with conventional pharmaceutical radioprotectors. Radioprotective agents offer several advantages in both oncotherapy and diagnostic applications. However, many synthetic radioprotectors are associated with limitations such as high cost, short duration of action, toxicity, and adverse effects on the central nervous system. In contrast, natural radioprotectors derived from plants have shown the potential to safeguard normal cells from radiation induced damage more effectively and safely than their synthetic counterparts. This review aims to identify safer and more effective radioprotective agents for use by oncologists and radiation biologists.